Transient Hypocalcemia in a Dialysis Patient With Paget's disease and Presumed Renal Cell Carcinoma - Kenneth R. Phelps MD; Jay Mo MD; Chrystina Czerwinskyj MD; Roy O. Mathew MD (SAGE Publishing, 2016)
A 68-year-old man with end-stage renal disease was hospitalized because of radicular pain and weakness in the left arm and hand. Sonography and computed tomography had recently shown a large right renal mass. On admission, magnetic resonance imaging demonstrated vertebral metastases with epidural extension, and radiotherapy was directed to the spine and kidney. Hypocalcemia was first noted on the fourth hospital day. A second computed tomography scan showed bleeding into and around the kidney, and arterial embolization was required to halt the bleeding. Hypocalcemia persisted for at least 27 days at values between 6.0 and 7.7 mg/dL and was consistently associated with ionized calcium concentrations less than or equal to 4.44 mg/dL. After an unrevealing search for a recognized cause, we attributed hypocalcemia to persistent sequestration of calcium in the right retroperitoneum. Exogenous supplementation eventually restored the concentration to normal. In the absence of renal and intestinal loss, hypocalcemia reflects abnormal flux of calcium from the extracellular compartment into tissue. Our patient's repository appears to have been a necrotic and hemorrhagic cancer. Tumor-induced sequestration of calcium should be included in the differential diagnosis of hypocalcemia.